Management information systems: Evaluating the adoption and impact of cloud computing in enterprise information systems - Faruque, Md Omar; Sharmin, Sadia; Talukder, Tughlok; Chowdhury, Saddam Nasir (Journal of Asian Business Strategy, 2024)
The objective of this study is to investigate the integration of cloud computing into business IT systems, with a specific focus on the motivations for this shift and its impact on company performance. The research employs a mixed-methods approach to investigate the relationship between company size, cloud service models, data transfer, and security concerns. Quantitative data was collected using a standardized questionnaire to evaluate the level of cloud computing adoption and its effects. Qualitative insights were obtained through semi-structured interviews with representatives from selected organizations. The study deliberately included organizations of different sizes and sectors to create a representative sample. The quantitative data was analyzed using statistical methods, which revealed intricate patterns in the adoption of cloud technology. On the other hand, the qualitative interviews were subjected to thematic analysis, which brought to light repeating themes and provided fresh insights into the usage of cloud computing. The incorporation of these data sets enabled a thorough comprehension of the function of cloud computing in modernizing company IT. This study aims to provide management information systems decision-makers and practitioners with valuable insights and actionable recommendations for effectively implementing cloud computing in various business scales and sectors. It offers a detailed analysis of cloud computing adoption, helping them navigate the complexities of cloud integration.